Marine and Offshore Renewable Energy (The Royal Institution of Naval Architects (RINA), 2012)
Marine and offshore renewable energy sources have the potential to make a significant contribution to the increasing total global demand, as well as meeting targets for clean energy. However, the demanding environment in which they are found presents great technological challenges for those who wish to develop such sources. Wave, tidal and offshore wind energy projects involve a wide range of disciplines and expertise. This conference brings together the industry stakeholders to provide a forum for discussion and a means of professional development for those involved with using natural marine resources to generate energy.